A feasibility study of some DSM enabling solutions in small islands: The case of Lampedusa. (1st December 2017) - Zizzo, G.; Beccali, M.; Bonomolo, M.; Di Pietra, B.; Ippolito, M.G.; La Cascia, D.; Leone, G.; Lo Brano, V.; Monteleone, F.
Abstract: The paper addresses the issue of the transition from a traditional electrical system without automation to a newer active and smart system allowing the possibility of implementing Demand Side Management policies, for little islands not supplied by the main grid. In particular, the paper focuses on two main topics related to the definition of: an effective control, monitoring and communication system as a tool for the full exploitation of the opportunities given by Demand Response policies; some solutions for the automation of the end-users' electrical installations, in order to offer to the utility flexibility to be used for the improvement of the generation and distribution efficiency. After a brief discussion on the international regulatory framework on automation and ICT applications for power systems, the paper presents a feasibility study, based on the characteristics of the island of Lampedusa, of a hierarchical architecture of a suitable control system and of some DSM enabling solutions for residential end-users. The proposed solutions are defined taking into account some main elements: distribution grids in small islands are generally equipped with outdated and hardly automatable devices; utilities in small islands have reduced budget for new investments; not less important, the most of the inhabitants has low income and unfamiliarity with automation. Therefore, main features of the proposed DSM enabling technologies are low cost and ease of use. Highlights: The paper focuses on ICT applications in small islands for improving energy efficiency. A not expensive ICT system's architecture for implementing DR policies is presented. BAC and TBM systems for energy savings are discussed. Two case studies on two real buildings are presented.